1988
DOI: 10.3109/10715768809066914
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescent and Respiratory Responses Related to Thyroid Hormone-Induced Liver Oxidative Stress

Abstract: Chemiluminescent and respiratory responses were studied in the liver of rats treated with 0.1 mg of triiodothyronine (T3)/kg for 1 to 7 days. Hyperthyroidism resulted in significant increments in the spontaneous chemiluminescence of the in situ liver in animals exhibiting a calorigenic response. Microsomal NADPH-dependent oxygen uptake was enhanced by T3 treatment for 2 days, an effect that was completely abolished by the antioxidant cyanidanol. A similar microsomal antioxidant-sensitive respiratory component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 19 publications
2
48
0
1
Order By: Relevance
“…Although all the extracts tested showed the ability to reduce lipid peroxidation by this method (Table 2), no significant differences were observed between them. Hydroperoxide-initiated chemiluminescence was more sensitive than TBARS production to determine changes in lipid peroxidation, as reported previously (24)(25)(26). Similarly, catechin was highly effective in inhibiting the hydroper- Table 1 -Antioxidant activity in extracts of P. peltata using the hydroperoxide-initiated chemiluminescence assay.…”
Section: Results and Discusionsupporting
confidence: 69%
“…Although all the extracts tested showed the ability to reduce lipid peroxidation by this method (Table 2), no significant differences were observed between them. Hydroperoxide-initiated chemiluminescence was more sensitive than TBARS production to determine changes in lipid peroxidation, as reported previously (24)(25)(26). Similarly, catechin was highly effective in inhibiting the hydroper- Table 1 -Antioxidant activity in extracts of P. peltata using the hydroperoxide-initiated chemiluminescence assay.…”
Section: Results and Discusionsupporting
confidence: 69%
“…Total SOD was found to decrease in liver [180] and increase in heart from young [120,157] but not from old [120] hyperthyroid rats.…”
Section: Antioxidant Statusmentioning
confidence: 82%
“…In some studies, it has been reported that SOD activity was significantly increased [12,179,181]. On the contrary, several authors reported that SOD activity were reduced in patients with hyperthyroidism [180,182].…”
Section: Antioxidant Statusmentioning
confidence: 97%
See 1 more Smart Citation
“…Hyperthyroidism has been associated with free radicalmediated damage to muscular tissues (7) and liver (20). Oxidative tissue injury is a secondary phenomenon to increased production of active oxygen species.…”
Section: Discussionmentioning
confidence: 99%